2011
DOI: 10.1143/jjap.50.08jf13
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Decomposition of Organic Compounds by Water Plasmas at Atmospheric Pressure

Abstract: The decomposition of acetone, methanol, and ethanol by water plasmas at atmospheric pressure has been investigated using a direct current (DC) discharge. At torch powers of 910–1050 W and organic compound concentrations of 1–10 mol %, the decomposition rate of methanol was over 99.99%, while those of acetone and/or ethanol was 96–99%. The concentrations of H2 obtained were 65–71% in the effluent gas and the removal efficiencies of 90–95% for total organic carbon (TOC) were achieved in liquid effluent for any c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Therefore, the water plasma system converts fluorinated compounds into environmentally benign and stable materials effectively with a high thermal efficiency of the torch and abundant radicals in the plasma flame. Furthermore, the water plasma torch has an advantage of direct use of a liquid waste as plasma supporting material instead of pure water [63][64][65]. For these reasons, the compact and energy efficient water plasma system can be effectively applied to treat a variety of waste including fluorinated compounds.…”
Section: Noble Plasma Torches For Decomposition Of Fluorinated Compoundsmentioning
confidence: 99%
“…Therefore, the water plasma system converts fluorinated compounds into environmentally benign and stable materials effectively with a high thermal efficiency of the torch and abundant radicals in the plasma flame. Furthermore, the water plasma torch has an advantage of direct use of a liquid waste as plasma supporting material instead of pure water [63][64][65]. For these reasons, the compact and energy efficient water plasma system can be effectively applied to treat a variety of waste including fluorinated compounds.…”
Section: Noble Plasma Torches For Decomposition Of Fluorinated Compoundsmentioning
confidence: 99%
“…This is because decomposition energy of D-glucose was required in the case of D-glucose solution. Although the temperature was decreased with injection of D-glucose solution, the arc temperature was sufficiently high The time constant at D-glucose decomposition process was estimated to be on millisecond order (Narengerile, 2011). This estimation suggests that the influence of arc fluctuation on the D-glucose decomposition is negligible.…”
Section: Results and Discussion 31 Temperature Fluctuationmentioning
confidence: 91%
“…The glycerine decomposition mechanisms as well as the intermediate behaviors were different from decomposition of organic compounds such as phenol [13] or acetone [18] by water plasmas. The negligible amount of soot generation from glycerine decomposition even at a low arc current indicated that a stronger oxidative atmosphere was formed which can enhance CH and CH 3 oxidation by OH radicals.…”
Section: Discussion On Decomposition Mechanismmentioning
confidence: 86%
“…A simplified decomposition reaction mechanism of glycerine solution in water plasmas was proposed on the basis of the results of the experiment and information from the literature [13,14,18] , as shown in Fig. 9.…”
Section: Discussion On Decomposition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation